FISCAL INSTRUMENTS FOR ENVIRONMENTAL SUSTAINABILITY: QUANTILE ANALYSIS OF ENVIRONMENTAL TAXES AND R&D IN G7 ECONOMIES - Abdulkadir BULUT (Sayıştay Dergisi)
Amid rising environmental challenges, G7 countries face mounting pressure to meet carbon neutrality targets. Fiscal policies, shaping both economic and environmental outcomes, are key to addressing these challenges. This study examines the joint impact of environmental taxes (ET) and public environment-related R&D (PERD) expenditures on the Load Capacity Factor (LCF) in G7 nations from 1994 to 2018. Using Method of Moments Quantile Regression (MMQR), results show that ET consistently improves LCF across all quantiles, supporting the Sustainable Development Goals, particularly SDG12 and SDG-13, by promoting behavioral change and industrial innovation. PERD, while less impactful at lower levels of sustainability, becomes increasingly effective in higher LCF quantiles—highlighting the importance of targeted R&D investments in renewable energy, sustainable agriculture, and carbon capture, aligned with SDG-7 and SDG-9. The GDP–LCF relationship confirms the Load Capacity Curve (LCC) hypothesis, while green innovation (GI) positively influences sustainability. Robustness checks (FMOLS, DOLS, CCR) confirm findings. The study calls for integrating revenue- and expenditurebased fiscal tools into unified sustainability strategies.